The crystal structure of 3-(1-(2-((5-methylthiophen-2-yl)methylene)hydrazinyl)ethylidene)chroman-2,4-dione, C17H14N2O3S - Radulović Niko S.; Sejmanović Dragana M.; Ristić Milenko N.; Dekić Vidoslav S.; Krüger Biljana; Kahlenberg Volker; Rodić Marko V. (Zeitschrift für Kristallographie - New Crystal Structures, 2022)
C17H14N2O3S, monoclinic, P21/c (no. 14), a = 9.8966(5) Å, b = 9.4360(4) Å, c = 16.7115(7) Å, β = 92.245(4)°, V = 1559.39(12) Å3, Z = 4, R gt(F) = 0.0358, wR ref(F 2) = 0.1013, T = 170 K.